Digital Interventions to Foster Adolescent Mental Health - Giandra, Fauzi; Shofiah, Nurul; Sholeha, Resti Muslimatus (Proceedings Conference Psychology and Flourishing Humanity, 2026)
The prevalence of mental health disorders among adolescents, including depression, anxiety, and stress, is rising globally, while access to face-to- face psychological services remains limited due to negative perceptions, cost, and a shortage of professionals. The advancement of digital technology has enabled the development of Digital Mental Health Interventions (DMHIs) that are more accessible and adaptable to adolescents’ lifestyles. This study employed a scoping review to provide an overview of publication trends and types of digital interventions supporting adolescent mental health from 2020– 2025. Following the Arksey and O’Malley framework and PRISMA-ScR guidelines, searches were conducted in the Springer and Garuda databases, identifying 17 studies meeting inclusion criteria. The review shows that the United Kingdom contributed the most publications consistently, while the United States and China have recently increased their participation. Identified interventions include mobile applications based on CBT, positive psychology, mindfulness, digital games, chatbots, web-based programs, and social media interventions. Mobile app-based interventions were the most common, addressing issues such as depression, anxiety, stress, loneliness, and substance abuse. Despite their potential, digital interventions face challenges including variability in effectiveness, lack of long-term data, and data privacy concerns. These findings underscore the significant potential of DMHIs as complementary to face-to-face services and highlight the need for global collaboration, adolescent-centered design, and further research with broader geographical coverage.